Sleep quality and associated factors amongst Brazilian physiotherapists during the COVID-19 pandemic. - Lino, Juliana A.; C. G. Frota, Luiza Gabriela; V. Abdon, Ana Paula; Cavalheri, Vinicius; Mont'Alverne, Daniela G. B.; Mesquita, Rafael (Physiotherapy Theory & Practice, 2022)
Objective: To investigate the prevalence of sleep problems and associated factors among Brazilian physiotherapists during the Coronavirus Disease 2019 (COVID-19) pandemic. Methods: Cross-sectional online survey of physiotherapists in Brazil. Sociodemographic data, sleep quality (Pittsburgh Sleep Quality Index – PSQI) and symptoms of anxiety, depression and stress (21-item Depression, Anxiety and Stress Scale – DASS-21) were assessed. Results: 342 physiotherapists responded the survey (18% male, median age 31 [27–38] years, 78% frontline workers). The three biggest fears reported by frontline physiotherapists were fear of being infected (48%), shortage of personal protective equipment (24%) and the severity of the disease (16%). The overall prevalence of poor sleep quality was 86%. Frontline physiotherapists showed worse scores on all PSQI components but sleep latency, disturbances and daytime dysfunction (p ≤ 0.037). Symptoms of anxiety and stress were highest in frontline workers (p ≤ 0.032). Being a frontline worker was independently associated with a poor sleep quality (odds ratio [95% CI] 1.99 [1.01 to 3.93]). Conclusion: Poor sleep quality was highly prevalent among Brazilian physiotherapists during the COVID-19 outbreak. Frontline physiotherapists showed worse sleep quality and more symptoms of anxiety and stress than non-frontline physiotherapists. Being at the frontline was associated with a higher chance of poor sleep quality.